Successful transplantation of kidneys from deceased donors with terminal acute kidney injury. (1st January 2019) - Domagala, Piotr; Gorski, Lukasz; Wszola, Michal; Kieszek, Rafal; Diuwe, Piotr; Goralski, Piotr; Drozdowski, Jakub; Ostaszewska, Agata; Gozdowska, Jolanta; Ciszek, Michal; Trzebicki, Janusz; Durlik, Magdalena; et al.
Abstract: Background: There are many doubts with regards to accepting deceased kidneys with acute kidney injury (AKI) for transplantation. Purpose: The aim of this study was to present the 5-years outcome of kidney transplantation cases where deceased donors developed AKI before organ procurement. Methods: Two hundred twenty-six deceased renal transplants were analyzed. Data regarding donors and recipients were collected. Terminal AKI was defined as terminal serum creatinine concentration higher than 1.99 mg/dL and 66 such cases were diagnosed. All kidney transplant recipients were followed for 60 months. Results: AKI group presented more episodes of delayed graft function (DGF) compared to the non-AKI group (56% vs 35%, p < .05). No differences were observed between the groups in the rate of acute rejection episodes, kidney function as well as patient and graft survival. Conclusions: Transplants with AKI present more often DGF and comparable graft survival to transplants without AKI. Kidneys with AKI can be a valuable source of organs provided attentive selection and appropriate care of deceased donors.